Applying The Art of War in The Battle for Patient Safety - Chew, Keng Sheng (UNIMAS Publisher, 2024)
Sun Tzu’s Art of War is perhaps one of the most popular ancient military treatise that has been accepted, translated, studied and applied in various non-military fields such as in management and business administration, politics, economics, sports, etc. Historically, the Art of War (Sun Zi Bing Fa 孫子兵法) was written approximately 2,500 years ago (512 BC) but it did not reach the West until 1772, when the text was translated into French by a French Jesuit called Father Jean Joseph Marie Amiot who had spent many years in Beijing.